Monetary Policy and Asset Prices : Does "Benign Neglect" Make Sense? - Jeanne, Olivier (IMF Working Papers; Working Paper, 2002)
The link between monetary policy and asset price movements has been of perennial interest to policymakers. In this paper, we consider the potential case for preemptive monetary restrictions when asset price reversals can have serious effects on real output. First, we present some stylized facts on boom-bust dynamics in stock and property prices in developed economies. We then discuss the case for a preemptive monetary policy in the context of a stylized model. We find that the optimal policy depends on the economic conditions in a complex, nonlinear way and cannot be summarized by a simple policy rule of the type considered in the inflation-targeting literature.